Determinación de las relaciones entre actores en el municipio Caibarién dirigido al fomento del desarrollo local del turismo - Cruz Bermúdez, Luis Daniel (Universidad Central "Marta Abreu" de la Villas, 2016)
The integration among the parts that are interested in the touristic development of one township represents an alternative of productive connections for development, by virtue of taking advantage of resources, potentialities and territorial capabilities as well as generating productivity improvements and innovations that foster the growth of business and the locality itself. A satisfactory integration level among the local actors in the township Caibarién would be a success for the tourist and local development of the territory, due to this, the purpose of this investigation was to determine the level of relationships among the interested parts in this township. For this, it were used as methods the Procedure proposed by Moya (2015) and the use of interviews, surveys and statistical methods for the obtaining, treatment and analysis of the information. As main results it were obtained that the territory has a wide range of potentialities (Natural, Historical-Cultural, Architectónics, Tangible and Intangible) that facilitate the local development in function of the tourist activity, but it also presents a scarce Tourist Infrastructure and Support Services, for what it could verify that although there is legitimate interests of the interested parts to develop the destination and having the same ones some resources, it exist low levels of relationships (economic, cooperation and collaboration) among some interested parts. To improve these relationships, that excessively they are a fundamental element in the use of these potentialities, it presents an actions set with the purpose of preparing the territory for future strategies that facilitate the local development of the township.
Keywords: Sistema Turístico; Destino Turístico; Caibarién; Turismo; Tourism; Desarrollo Local; Local Development